Advancements in neuroscience for healthcare: recent innovations and breakthroughs in mental health treatment - Sinha, Rashmi; Kumar Sahu, Kishor (Journal of Neonatal Surgery, 2025)
The field of neuroscience has witnessed significant advancements in recent years, particularly in the realm of mental health treatment. This paper explores the latest innovations and breakthroughs in neuroscience that are shaping the landscape of mental health care. These advancements include the development of neuroimaging techniques, precision medicine approaches, and novel therapeutic interventions such as neurostimulation and neuromodulation. The integration of artificial intelligence (AI) and machine learning has further enhanced diagnostic accuracy and treatment personalization. This study provides a comprehensive overview of recent research, focusing on how these advancements are addressing various mental health disorders, including depression, anxiety, bipolar disorder, and neurodevelopmental disorders. Additionally, the ethical considerations and future challenges associated with these technologies are discussed. By fostering a deeper understanding of the underlying neural mechanisms, neuroscience is paving the way for more effective, targeted, and individualized mental health treatments.